Differential effect of intrauterine growth restriction on childhood neurodevelopment: a systematic review. (19th May 2015) - Murray, E; Fernandes, M; Fazel, M; Kennedy, SH; Villar, J; Stein, A
<x xml:space="preserve">Abstract</x> Background Neurodevelopmental disorders are increasingly believed to originate from intrauterine growth restriction (IUGR). Current reviews exploring the neurodevelopmental effects of IUGR, however, are mostly based on birthweight, an inadequate proxy. Objective We aimed to examine the association between IUGR documented in utero, and neurodevelopmental outcomes during childhood. Search strategy Medline, CINAHL, PsycInfo and Scopus were searched for relevant studies published after 1970. Selection criteria The analysis included studies that identified IUGR in utero, with follow‐up assessments between 1 month and 12 years of age. Data collection and analysis Data was extracted for cognitive, behavioural, language, motor, hearing, vision or sleep outcomes. Studies were summarised separately for children born at <35 and ≥35 weeks gestation. Main results Of 28 876 titles identified, 38 were suitable for inclusion. IUGR children born ≥35 weeks gestation scored on average 0.5 SD lower than non‐IUGR children across all neurodevelopmental assessments. IUGR children born <35 weeks of gestation scored approximately 0.7 SD lower than non‐IUGR children across all neurodevelopmental assessments. IUGR children with evidence of fetal circulatory redistribution (preferential perfusion of the brain) had more severe neurodevelopmental impairments than those born IUGR alone. Conclusions IUGR increases the risk of neurodevelopmental impairment during childhood differentially across domains. IUGR children born preterm or with evidence of fetal circulatory redistribution are more severely affected. Tweetable abstract IUGR is associated with an overall risk for neurodevelopmental delay in a range of neurodevelopmental domains.